The waterfall model with agile scrum as the hybrid agile model for the software engineering team - Yahya, Norzariyah; Maidin, Siti Sarah (IEEE, 2022)
Hybrid agile is a software development model that combines the agile approach with a non-agile development strategy. A software engineering team chooses the hybrid agile to best fit the development process based on project needs; some projects require a plan-driven approach, and at the same time, agility is a must. However, among many agile methodologies and plan-driven development models, which methodologies or models adopted by a software engineering team lead to hybrid agile. This research aims to identify the software engineering team’s approach and model that resulted in the emergence of a hybrid agile model. Data for this research were acquired through a qualitative study using interviews as the data collection instrument and thematic analysis is used to analyze the data and identify the theme. In the context of this paper, we focus on only one (1) theme, which is “models used in a software project”. According to the research findings, the agile Scrum and Waterfall models are the models that have been practised in software projects that have resulted in the hybrid agile model. In the near future, further research will be conducted to determine which process model is employed in certain software process phases of a software project.